Single-particle and collective excitations in the transitional nucleus 166Os. (11th October 2021) - Stolze, S; Grahn, T; Julin, R; Joss, D T; Andgren, K; Auranen, K; Bönig, S; Cox, D; Darby, I G; Doncel, M; Eeckhaudt, S; Greenlees, P T; et al.
Abstract: The mean lifetimes of the lowest energy 2 +, 8 + and 9 − states in 166 Os have been measured using the recoil distance Doppler-shift method in conjunction with a selective recoil-decay tagging technique. These measurements extend studies into the most neutron-deficient mass region accessible to current experimental methods. The B ( E 2; 2 + → 0 + ) = 7(2) W.u. extracted from these measurements is markedly lower than those observed in the heavier even-mass Os isotopes. The 8 + and 9 − states yield reduced transition probabilities that are consistent with single-particle transitions. While these values may indicate a departure from collective structure, the level scheme and the underlying nuclear configurations can also be interpreted in terms of a simple collective picture. This contrasting behaviour suggests an intriguing dichotomy in the description of heavy transitional nuclei.